2021
DOI: 10.1108/ijoa-09-2020-2409
|View full text |Cite
|
Sign up to set email alerts
|

Wisdom capital: definitions, meaning and a two-level model

Abstract: Purpose Anecdotal evidence suggests the growing need for wise people and organizations, which are fully dedicated to building up the greater good more than ever before. The purpose of this study is to broaden the role of wisdom by triggering an aware and genuine concern toward building wisdom capital (WC) within organizations. Design/methodology/approach First, this endeavor draws upon key issues of wisdom theory literature, namely, the nuances of its general aspects, basic components, other relevant issues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…The results obtained by the research of Hånell et al . (2021), Vasconcelos (2021), Pauleen and Intezari (2019) and Ghorbani and Khormaei (2018) correspond.…”
Section: Discussionmentioning
confidence: 94%
“…The results obtained by the research of Hånell et al . (2021), Vasconcelos (2021), Pauleen and Intezari (2019) and Ghorbani and Khormaei (2018) correspond.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, KM authors began to focus on understanding the human factors, processes, context and interactions in knowledge creation (Bencsik et al , 2020; Jakubik, 2007, 2011; Nonaka et al , 2008, 2014; Nonaka and Takeuchi, 2011; Nonaka and Toyama, 2002; Serenko, 2013, 2021; Serenko and Bontis, 2017, 2021; Vasconcelos, 2021). Since year 2000, Nonaka et al (2008) demonstrated the importance of practical wisdom ( phronesis ) and wise leadership in KM.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the economic consequences of trust and distrust in knowledge-intensive organisations (Bencsik et al , 2020), and the importance of human values and human interactions in KM research. Furthermore, Vasconcelos (2021) proposed the wisdom capital concept, which is highly relevant to KM, and presented his two-level model. He argued that individual wisdom capital (IWC) means doing good, doing right, excellence, improving society, serving others and oneself and organisational wisdom capital (OWC) includes greater good, common good, human good and well-being.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jeste et al (2019) list the following attributes: compassion, self‐reflection, uncertainty acceptance, spirituality and decisiveness. Vasconcelos (2022) asserted that wise people have the right expertise and knowledge to handle concrete challenges and can form proper solutions in novel situations and take action.…”
Section: Literature Reviewmentioning
confidence: 99%